(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This paper tried to explore the view of religious and non-religious people on severity of coronavirus disease 2019 in South Korea. Authorsemploys a survey method to investigate if religious people in South Korea have different opinions about the risk and dangers of coronavirusdisease 2019 compared to non-religious people. The samples for this research were collected via Google Form and paper-pencil based fromthe university students of Korea. Correlation coefficient tests was performed and the difference-of-means t-test to see if there was asignificant correlation between religiosity and the belief that the coronavirus is dangerous. The results showed that is no strong evidence tosupport our hypothesis.